Investigation of transdermal permeation behavior of diclofenac sodium microemulsion by confocal laser scanning microscopy - Hui Yang; Prapaporn Boonme; Thanaporn Amnuaikit (Polskie Towarzystwo Farmaceutyczne, 2023)
Purpose: To investigate the in vitro skin permeation and transdermal behavior of diclofenac sodium using a new system of microemulsion. Methods: Diclofenac sodium was incorporated into oil-in-water (o/w) and water-in-oil (w/o) microemulsions consisting of a 2:1 ratio of Cremophor RH 40: Span 80 as surfactant phase, ethylhexyl palmitate as oil phase, and a 2:1 ratio of water: isopropanol as aqueous phase. Franz diffusion cell was used to determine the in vitro skin permeation. Morphology of microemulsions were characterized by transmission electron microscopy (TEM). The depth of penetration distribution was visualized by fluorescently labelling, and observing using confocal laser scanning microscopy (CLSM). Results: The o/w type provided an enhanced permeation flux, with more than a 3- fold increase in permeability coefficient across skin as compared with w/o type. The morphology characterization indicated that both o/w and w/o type were nano-sized and spherical in shape. It was observed by CLSM that o/w type significantly facilitated the penetration of sulforhodamine B (SRB) to the deeper layers of the skin (220 μm) than w/o type (150 μm). Conclusion: This study demonstrates that diclofenac sodium microemulsion can be transdermal, and the skin penetration depends on the microstructure and composition of microemulsion.